S117 Respiratory muscle fatigue following exercise in patients with interstitial lung disease. (2nd December 2011) - Elia, D; Kelly, J L; Martolini, D; Renzoni, E; Boutou, A K; Chetta, A; Polkey, M I; Hopkinson, N S
Abstract : Background: Patients with interstitial lung disease (ILD) experience progressive breathlessness and exercise limitation. Although respiratory muscle fatigue has been investigated in healthy subjects and patients with COPD, it is unknown whether it occurs during exercise in ILD patients and, if so to what extent it is related to changes in dynamic lung volumes. Methods: Patients with ILD performed incremental, symptom-limited cycle ergometry with inspiratory capacity manoeuvres used to measure changes in end-expiratory lung volume (EELV). Twitch transdiaphragmatic pressure (TwPdi), in response to bilateral anterolateral magnetic phrenic nerve stimulation and twitch gastric pressure (TwT10 Pga) in response to magnetic stimulation over the 10th thoracic vertebra were used to assess the development of fatigue. Results: Sixteen ILD patients (11 women) were studied. TwPdi did not differ significantly pre and post exercise (21.8±8 vs 20.2±8 cmH2 O; p=0.10), while TwT10 Pga fell from 28.6±18 to 25.2±14 cmH2 O (p=0.02) (Abstract S117 figure 1 ). EELV fell from 2.18±0.65 l to 1.91±0.59 l following exercise (p=0.04). The fall in TwT10Pgas correlated with peak VO2 (r=−0.52, p=0.041) increase in heart rate (r=0.53 p=0.032) and with the decrease of EELV during exercise (r=0.57, p=0.021). Abdominal muscle fatiguers (n=9, 56%), defined as a ≥10% fall in TwT10Pga, had a fall in EELV of 22±22% compared to 0.7±8% in non-fatiguers (p=0.016). Conclusion: Abdominal muscle fatigue develops during exercise in ILD patients in association with increased expiratory muscle activity manifest by reduced EELV.